`int1/(x^2-4x+9)dx`

Let's complete the square for the denominator of the integral as:

`(x^2-4x+9)=(x-2)^2+5`

`(x-2)^2+(sqrt(5))^2`

`int1/(x^2-4x+9)dx=int1/((x-2)^2+(sqrt(5))^2)dx`

Let's apply the integral substitution,

substitute `u=x-2`

`du=1dx`

`=int1/(u^2+(sqrt(5))^2)du`

Now use the standard integral :`int1/(x^2+a^2)=1/aarctan(x/a)`

`=1/sqrt(5)arctan(u/sqrt(5))`

substitute back u=(x-2) and add a constant C to the solution,

`=1/sqrt(5)arctan((x-2)/sqrt(5))+C`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.